Impact of contrast medium osmolality on the risk of acute kidney injury after transcatheter aortic valve implantation: insights from the Magna Graecia TAVI registry. (15th April 2021) - Iacovelli, Fortunato; Pignatelli, Antonio; Cafaro, Alessandro; Stabile, Eugenio; Salemme, Luigi; Cioppa, Angelo; Pucciarelli, Armando; Spione, Francesco; Loizzi, Francesco; De Cillis, Emanuela; Pestrichella, Vincenzo; Bortone, Alessandro Santo; et al.
Abstract: Background: Acute kidney injury (AKI) after transcatheter aortic valve implantation (TAVI) is frequent and associated with adverse outcomes and mortality; to date, in such setting of patients there is no consistent evidence that either low-osmolar contrast media (LOCM) or iso‐osmolar contrast medium (IOCM) are superior to the other in terms of renal safety. Methods: 697 consecutive patients not in hemodialysis treatment who underwent TAVI (327 males, mean age 81.01 ± 5.75 years, mean european system for cardiac operative risk evaluation II 6.17 ± 0.23%) were enrolled. According to osmolality of the different iodinated CM, the population was divided in 2 groups: IOCM ( n = 370) and LOCM group ( n = 327). Preoperatively, 40.54% of patients in IOCM vs 39.14% in LOCM group ( p = 0.765) suffered from chronic kidney disease (CKD). Results: The incidence of AKI was significantly lower with IOCM (9.73%) than with LOCM (15.90%; p = 0.02), and such significant difference ( p < 0.001) in postprocedural change of renal function parameters persisted at discharge too. The incidence of AKI was also significantly lower with IOCM in younger patients, without diabetes, anemia, coronary artery disease history, CKD, chronic or persistent atrial fibrillation, left ventricular ejection fraction ≤35%, and in patients with low operative mortality risk scores, receiving lower amounts of dye ( p < 0.05 for all). Importantly, multivariate analysis identified LOCM administration as an independent risk factor for both AKI ( p = 0.006) and 1-year mortality ( p = 0.001). Conclusions: The use of IOCM have a favorable impact on renal function with respect to LOCM, but it should be considered especially for TAVI patients at lower AKI risk.